2021
DOI: 10.7150/jca.51567
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic values of transfer RNA-derived fragment tRF-19-3L7L73JD and its effects on the growth of gastric cancer cells

Abstract: Background and aim: Medicine has made great progress, but gastric cancer is still one of the most common malignant tumors worldwide. tRNA-derived fragments (tRFs), a type of small non-coding RNA, have been found to play important roles in cancers. Due to an abundance of modifications, tRFs have the potential to serve as cancer biomarkers. However, the relationship between tRFs and gastric cancer is still largely unclear. We have identified a new tRF, tRF-19-3L7L73JD, found to be expressed at a lower level in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Seven studies 11 , 29 , 33 , 34 , 35 , 36 , 37 used a genome‐wide discovery approach with high throughput sequencing or small RNA sequencing to identify candidate tRFs, which were then validated in an independent cohort using qRT‐PCR. Using this approach, three of these three studies 11 , 32 , 33 selected a panel of tRFs to distinguish GC from normal controls. Table 1 summarizes the study's characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies 11 , 29 , 33 , 34 , 35 , 36 , 37 used a genome‐wide discovery approach with high throughput sequencing or small RNA sequencing to identify candidate tRFs, which were then validated in an independent cohort using qRT‐PCR. Using this approach, three of these three studies 11 , 32 , 33 selected a panel of tRFs to distinguish GC from normal controls. Table 1 summarizes the study's characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al found that tRF‐19‐3L7L73JD suppresses cell proliferation as well as migration, induces apoptosis, and arrests cells at the G0/G1 phases, implying inhibitory roles in GC development. 32 …”
Section: Introductionmentioning
confidence: 99%
“…Some sncRNAs not only can promote cell proliferation as a carcinogen, but also inhibit the development of cancer as an inhibitor. For instance, tRF-19-3L7L73JD derived from tRNA-Val-AAC can inhibit the development of gastric cancer by blocking cell proliferation in G0/G1 phase 61. Downregulation of SNORA42 can inhibit non-small cell lung cancer cell proliferation by inducing p53-dependent apoptosis 62.…”
Section: Biological Function Of Sncrnas In Cancermentioning
confidence: 99%
“…sncRNAs can be detected not only in tumour tissues but also in circulating blood. According to the unique expression pattern between cancer and normal specimens and the correlation with clinicopathological features, sncRNAs have become an ideal biomarker platform for cancer diagnosis 52 61 80–83. For example, U6 snRNA was significantly upregulated in cervical cancer, and the degree of upregulation was positively correlated with the stage of cancer 84.…”
Section: Clinical Significance Of Sncrnas In Cancermentioning
confidence: 99%
“…Another study found that the tRF-3017A derived from tRNA Val−TAC can combine with AGO protein to regulate the expression of cancer suppressor gene NELL2, which promotes migration of GC cells and metastasis of lymph nodes in GC patients, and has the effect of facilitating GC malignant progression [ 29 ]. Besides, the expression of tRF-19-3L7L73JD was decreased in GC, which could block the GC cell cycle in the G0/G1 phase, induce apoptosis, inhibit cell proliferation and migration, and thus inhibit the malignant progression of GC [ 78 ]. Moreover, tsRNAs can also influence the progression of GC by regulating signaling pathways.…”
Section: Dysregulation Of Tsrnas In Cancer and Related Rolesmentioning
confidence: 99%